Bangladesh : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
The Sixth Five Year Plan, as outlined in Bangladesh's Poverty Reduction Strategy Paper, targets strategic growth and employment. The medium-term macroeconomic framework plan entails the involvement of both the private and public sectors. Human resources development strategy programs reaching out to the poor and the vulnerable population, as well as environment, climate change, and disaster risk management, have been included in the plan. Managing regional disparities for shared growth and strategy for raising farm productivity and agricultural growth have been outlined. Diversifying exports and developing a dynamic manufacturing sector are all inclusive in the proposed plan.